The given equation is:
![y=(2x+5)(x-1)](https://img.qammunity.org/2023/formulas/mathematics/college/h0rpb5utxq1tz2i3qmjzu72006yy1tgq1w.png)
We need to transform it into the form:
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
We can do it by multiplying the parentheses:
![\begin{gathered} y=2x\cdot x-2x\cdot1+5\cdot x-5\cdot1 \\ y=2x^2-2x+5x-5 \\ y=2x^2+3x-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bdejy5zgg3bw3hpo4hekmfz5wfb08g3eyj.png)
Then a=2, b=3 and c=-5.
The vertex of the parabola is given by (h,k) where:
![\begin{gathered} h=-(b)/(2a) \\ k=f(h) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dq5m36ed5wdkdtjzqqa2mkdcbpvwjiwrql.png)
Then h and k are equal to:
![\begin{gathered} h=-(3)/(2\cdot2)=-(3)/(4)=-0.75 \\ k=f(-0.75) \\ \therefore k=2\cdot(-0.75)^2+3(-0.5)-5 \\ k=1.125-2.25-5 \\ k=-6.13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/27z2uqxbhvqkqq0jrf989898dmht25tejx.png)
Thus, the vertex is at (-0.75, -6.13).
Now, to find the zeros of the function, we can use the quadratic formula:
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
By replacing the know values we obtain:
![\begin{gathered} x=\frac{-3\pm\sqrt[]{3^2-4(2)(-5)}}{2(2)} \\ x=\frac{-3\pm\sqrt[]{9+40}}{4} \\ x=\frac{-3\pm\sqrt[]{49}}{4} \\ x=(-3\pm7)/(4) \\ \text{Then x is equal to:} \\ x=(-3+7)/(4)=(4)/(4)=1\text{ and }x=(-3-7)/(4)=(-10)/(4)=-2.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/osujbb9mkz3jqmvv5mo5dqj4idr4llpxav.png)
Thus, the zeros are at: (-2.5,0) and (1,0).
Answer: the graph that represents the parabola is the last one with the vertex at (-0.75, -6.13) and the zeros at (-2.5,0) and (1,0).